Trade costs in the global economy: Measurement, aggregation and decomposition - Peter Egger; Mario Larch; Sergey Nigai; Yoto Yotov (World Trade Organization (WTO), 2021)
Proper measurement and aggregation of trade costs is of paramount importance for sound academic and policy analysis of the determinants - particularly those of policy - of economic outcomes. The international trade profession has witnessed significant new developments, both on the theoretical and on the empirical side, concerning the measurement and decomposition of such costs into variable and fixed costs on the one hand and into partial and general equilibrium effects on the other hand. The objectives and main contributions of this project are to offer guidance for proper measurement, aggregation, and decomposition of trade costs into fixed vs. variable and partial vs. general equilibrium costs across two broad dimensions, one including overall trade costs vs. policy measures vs. transportation costs vs. natural trade barriers vs. uncertainty and another one including geography vs. product vs. household income level vs. agent.
Keywords: C23; C31; F1; 330; Trade costs; Structural gravity; Multi-sector and multi-country models; Heterogeneous firms; Panel data; Measurement; Aggregation; Decomposition